A Conserved EAR Motif Is Required for Avirulence and Stability of the Ralstonia solanacearum Effector PopP2 In Planta - Segonzac, Cécile; Newman, Toby E.; Choi, Sera; Jayaraman, Jay; Choi, Du Seok; Jung, Ga Young; Cho, Heejung; Lee, Young Kee; Sohn, Kee Hoon (Frontiers in Plant Science, 2017)
Ralstonia solanacearum is the causal agent of the devastating bacterial wilt disease in many high value Solanaceae crops. R. solanacearum secretes around 70 effectors into host cells in order to promote infection. Plants have, however, evolved specialized immune receptors that recognize corresponding effectors and confer qualitative disease resistance. In the model species Arabidopsis thaliana, the paired immune receptors RRS1 (resistance to Ralstonia solanacearum 1) and RPS4 (resistance to Pseudomonas syringae 4) cooperatively recognize the R. solanacearum effector PopP2 in the nuclei of infected cells. PopP2 is an acetyltransferase that binds to and acetylates the RRS1 WRKY DNA-binding domain resulting in reduced RRS1-DNA association thereby activating plant immunity. Here, we surveyed the naturally occurring variation in PopP2 sequence among the R. solanacearum strains isolated from diseased tomato and pepper fields across the Republic of Korea. Our analysis revealed high conservation of popP2 sequence with only 3 polymorphic alleles present amongst 17 strains. Only one variation (a premature stop codon) caused the loss of RPS4/RRS1-dependent recognition in Arabidopsis. We also found that PopP2 harbors a putative eukaryotic transcriptional repressor motif (ethylene-responsive element binding factor-associated amphiphilic repression or EAR), which is known to be involved in the recruitment of transcriptional co-repressors. Remarkably, mutation of the EAR motif disabled PopP2 avirulence function as measured by the development of hypersensitive response, electrolyte leakage, defense marker gene expression and bacterial growth in Arabidopsis. This lack of recognition was partially but significantly reverted by the C-terminal addition of a synthetic EAR motif. We show that the EAR motif-dependent gain of avirulence correlated with the stability of the PopP2 protein. Furthermore, we demonstrated the requirement of the PopP2 EAR motif for PTI suppression. A yeast two-hybrid screen indicated that PopP2 does not interact with any well-known Arabidopsis transcriptional co-repressors. Overall, this study reveals high conservation of the PopP2 effector in Korean R. solanacearum strains isolated from commercially cultivated tomato and pepper genotypes. Importantly, our data also indicate that the PopP2 conserved repressor motif could contribute to the effector accumulation in plant cells.